Pembelajaran Berbasis Ekopesantren: Studi Pembelajaran Teritegrasi Pesantren dengan Lingkungan Agraris Mata Pelajaran Fiqih di MA Plus Sunan Drajat 7 - Mustafa Ali Maskur; Nur Khofifatun Nisah (An-Nahdloh: Journal of Education and Islamic Studies, 2026)
This study aims to analyze the concept and forms of integrating ecopesantren-based learning into the Fiqh subject at MA Plus Sunan Drajat 7, as well as its impact on students’ ecological awareness. This research employs a qualitative approach using a case study method. Data were collected through classroom observations, in-depth interviews with Fiqh teachers, the head of the madrasah, and students, as well as documentation studies including lesson plans (RPP) and learning activity archives. Data analysis was conducted through data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation.the findings indicate that ecopesantren-based Fiqh learning at MA Plus Sunan Drajat 7 is integratively designed by utilizing the pesantren’s agrarian environment, such as gardens, rice fields, and natural resources, as contextual learning media. The integration of learning is implemented through hands-on practices in the topics of thaharah, muamalah, and agricultural zakat, which are linked to farming activities and environmental management. This learning approach enhances students’ applied understanding of Fiqh and fosters environmental awareness. Students not only comprehend Islamic legal principles cognitively but also practice them in their daily lives. Therefore, ecopesantren-based learning is proven to be effective in shaping both students’ religious character and sustainable ecological awareness. Keywords: ecopesantren, Fiqh learning, agrarian environment, ecological awareness, pesantren